2017
DOI: 10.1002/pon.4592
|View full text |Cite
|
Sign up to set email alerts
|

Should consultation recording use be a practice standard? A systematic review of the effectiveness and implementation of consultation recordings

Abstract: Consultation recordings are valuable to patients and positively associated with patient-reported outcomes. Successful integration of consultation recording use into clinical practice requires an administratively supported, systematic approach to addressing implementation factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 47 publications
2
40
0
7
Order By: Relevance
“…The main results of this review are consistent with previous reviews among other patient populations (Pitkethly et al, 2008;Rieger et al, 2018;Tsulukidze et al, 2014;van der Meulen, Jansen, van Dulmen, Bensing, & van Weert, 2008;Watson & McKinstry, 2009). Similar to previous reviews, we have shown that the primary value of consultation recording is to increase patient satisfaction and recall.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The main results of this review are consistent with previous reviews among other patient populations (Pitkethly et al, 2008;Rieger et al, 2018;Tsulukidze et al, 2014;van der Meulen, Jansen, van Dulmen, Bensing, & van Weert, 2008;Watson & McKinstry, 2009). Similar to previous reviews, we have shown that the primary value of consultation recording is to increase patient satisfaction and recall.…”
Section: Discussionsupporting
confidence: 90%
“…Another concern among doctors, presumably the most important concern, is the issue of privacy and legislation. Our review has not focussed on these concerns of doctors, but the literature review of Rieger et al (2018) has provided useful recommendations to deal with medico-legal concerns. These recommendations could help to successfully implement consultation recording in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, test providers should also produce written information materials for patients that could help oncologists to explain the nature of the tests being performed as well as the results. There could be a potential value in providing the patients with the audio‐recordings of the oncological consultations in which genomic results are discussed …”
Section: Resultsmentioning
confidence: 99%
“…While the studies do not provide a conclusive answer as to whether computers improve the physician-patient interaction or not [2,11,28], they make clear that the use of technology is growing reading or filling out medical records amounts to 25% of consultation time and covers over 40 specific activities [21]. Physicians also record their consultations in an audio or video format to make the documentation processes less interruptive for the communication with the patients, although this practice remains controversial [29]. Technologies expected to enter the consultations are double checks / clinical diagnosis decision support systems in which AI supports the physician with the interpretation of proper symptoms and treatment choice, but how they will impact the interaction with the patient remains unclear [33].…”
Section: Existing Solutionsmentioning
confidence: 99%